Use of oclacitinib in the treatment of vesicular cutaneous lupus erythematosus in a Border Collie breed dog – case report (Research, Society and Development, 2022)
Vesicular cutaneous lupus erythematosus (VCLE) is a rare autoimmune inflammatory skin disease, a unique subacute variant of canine cutaneous lupus erythematosus. It affects adult Collie, Shetland Shepherd, Border Collie dogs and their crosses. In general, VCLE requires immunosuppressive treatments, which cause side effects and non-homogeneous therapeutic efficacy. A Border Collie dog, male, 3 years old, was diagnosed with VCLE. It showed a moderate response to the therapeutic combination of tetracycline-nicotinamide and later cyclosporine-ketoconazole. The objective of this study was to report the therapeutic success obtained with the use of oclacitinib, a Janus kinase inhibitor, in the control of VCLE lesions. The drug was administered at a dose of 0.6 mg/kg, orally, every 12 hours for 15 days and then every 24 hours for additional 20 days. Complete clinical resolution was observed in a few days, effectively and apparently without adverse effects. It is concluded that oclacitinib may be an advantageous alternative in the treatments of this variant of canine cutaneous lupus erythematosus. However, further studies on the use of Janus kinase inhibitors in the control of canine dermatological autoimmune diseases are needed.